Baohuoside I Inhibits the Proliferation of Hepatocellular Carcinoma Cells via Apoptosis Signaling and NF‐kB Pathway. Issue 6 (27th April 2021) - Sun, Yunlong; Pang, Bo; Wang, Yingzhe; Xiao, Jinglei; Jiang, Dacheng
Abstract: Baohuoside I is a flavonoid isolated from Epimedium koreanum Nakai and has many pharmacological activities. However, its role in liver cancer remains unclear. This study aimed to investigate the inhibitory effect of Baohuoside I on the Human Hepatocellular Carcinoma (HCC) cell lines QGY7703, and underlying mechanisms. QGY7703 cells were used as the model to assess the function of Baohuoside I in vitro . The effects of Baohuoside I on QGY7703 cells' growth, proliferation, and invasiveness were confirmed by CCK‐8, lactate dehydrogenase release, and invasion assays. Cell apoptosis was analyzed by flow cytometry, and the levels of cleaved Caspase‐3, Bax, and Bcl‐2 were quantified by western blot. Western blot analysis, nuclear translocation of NF‐κB, and Q‐PCR were used to measure the expression of affected molecules. In QGY7703 cells, Baohuoside I induced the expression of molecules related to NF‐κB pathway. The toxicity of Baohuoside I on QGY7703 cells was also confirmed in vivo, in a tumor model. Baohuoside I had a significant toxic effect on QGY7703 cells from a concentration of 10 μM. This compound significantly inhibited the proliferation of QGY7703 cells by inducing apoptosis and downregulating NF‐κB signaling pathway. Thus, Baohuoside I is a novel candidate drug and opens new possibilities of clinical strategies for HCC treatment. Abstract :